Infusing Vibrancy into Science Learning through Weismann: An Educational Game for Learning Plants and Animals’ Reproduction Systems - Annisa, Nurul; Lestari, Tuti (SEAMEO QITEP in Science, 2024)
This research endeavours to develop an educational game, Weismann, designed to enhance the engagement and effectiveness of teaching and learning about plants and animals’ reproduction systems. Named after August Friedrich Leopold Weismann, the pioneering scientist behind the germplasm theory, the game aims to infuse vibrancy into the learning experience. Adopting a Research and Development (R&D) framework, the study employs sourced data from multiple channels, including expert validation assessment scales as well as science teachers and their students’ feedback on their practical experiences as users. The findings reveal Weismann to be highly valid, scoring 91.2, and remarkably practical, with teachers and students rating it at 95.9 and 83.9, respectively. These results affirm the game’s efficacy as a valuable tool for science education, offering a dynamic and effective approach to learning.